Growth and maturation processes of purple passion fruit (Passiflora edulis sims) through physical and metabolomics approaches - Md. Nor, Shahidah (2021)
The purple passion (Passiflora edulis SIMS) fruit has enormous potential to be cultivated on a mass scale in Malaysia since it gains high demand in the global market. This study is aimed to understand the growth and maturation process of passion fruit through physical and metabolomics approaches for producing high quality fruit for fresh fruit and varieties of industries. Growth and development of passion fruit were tracked starting from 7 days after anthesis (DAA) until the fruit detached from the plant. The first study was conducted to establish the fruit optimal harvesting stage. Logistic model showed all physical traits of passion fruit fitted well with single sigmoid curve with high regression coefficient (R2) around 0.984-0.992. The anatomical study showed that passion fruit have three distinct growth phases; stage 1 (S1) (0-7 DAA), stage 2 (S2) (14-28 DAA) and stage 3 (S3) (35-63 DAA). Purple passion fruit obtained maturity at 49 DAA and ripened at 56 DAA. The S3 phase was investigated intensively in studies 2 and 3 because it is a vital period for maturation and ripening. In the second and third studies, metabolomics approaches have been implemented in studying the dispersion of metabolites during maturation and ripening process. In the study 2, juice and seed were subjected to 1H NMR analysis as both compartments play significant role in fruit eating quality. Around 30 and 32 metabolites were found in juice and seed, respectively. Result showed the primary metabolites dominating both compartments consist of sugar (glucose, sucrose, fructose), organic acid (tartaric acid, citric acid, malic acid) and amino acid (lysine, threonine, methionine, leucine) while secondary metabolites present as minor compounds (chlorogenic acid, epicatechin and phenylacetic acid). Segregating the metabolites using principal component analysis (PCA) and partial least square discriminant analysis (PLS-DA) have outlined how the metabolites in both compartments changed dynamically throughout the maturation and ripening process. Variable importance in the projection (VIP) has sorted 13 and 18 metabolites as highly influential metabolites in juice and seed. Glycolysis, TCA cycle, shikimate pathway, ethylene and polyamine were detected as important biochemical pathways that were responsible for the fruit's maturation and ripening. The third study analysed juice, seed and peel since all fruit compartments have equal benefits to be exploited as industrial products. Result showed that each fruit compartments have different secondary metabolites contents correlated with their antioxidant activity. During ripening, β-carotene and chlorophyll pigments degraded while anthocyanin accumulated, resulting peel in a deep purple. The peel was abundant with different types of phenolic acid (chlorogenic acid, caffeic acid and its derivatives) and flavonoid components (isorientin, rutinoside and vitexin-2''-O-rhamnoside) possessed the highest antioxidant activity determined by FRAP (732.91- 1089.61 μmol TE. 100 g-1 FW), ABTS (62.34-70.10 μmol TE. g-1 FW) and DPPH (52.362- 67.66 μmol TE. g-1 FW) as compared to seed and juice. All passion fruit compartments should be completely exploited for fresh consumption and product manufacturing. Hence, herein a comprehensive view of passion fruit growth and development may benefit Malaysia's agriculture and processing industries.